Importance of quality fodder for higher milk production in dairy animals - Singh, Sukhjinderjit; Rajni, Rajni (Indian Farming, 2018)
To improve nutritional worth of the fodder which makes the feed more digestible, palatable and nutritious, crop mixtures consisting of both legumes and non-legumes should be grown together. Secondly, to produce high quality forage and to get more milk per animal by exploiting its genetic potential, harvesting of fodder crops should be done at optimum stage of maturity. This is because harvesting at optimum stage not only provides better nutrition to animals for higher milk production but also saves the animals from various nutritional related health hazards caused due to anti-quality components (prussic acid, oxalates and nitrates) present in it. Only quality forage which is a cheapest source of nutrients for milch animals can keep dairy farmers in this business forever.